Fiatures of realization of method of planning in activity of permanent commissions of local advices - Набока, І. В. (Theory and practice of jurisprudence, 2016)
Тhe article investigational and exposed planning essence as an organizational method of activity of permanent commissions of local advices, author approach is certain, description of the current and perspective planning is given, the form of drafting of plans of work of permanent commissions is offered